Pengembangan Game Pembelajaran IPAS Pada Siswa SD Berbasis Kearifan Lokal Pendekatan Konteksual - Amelia, Amelia; Lestari , Neta Dian; Syaflin , Sylvia Lara (Jurnal Ilmiah Profesi Pendidikan, 2025)
The problem in this study is that it is still difficult to understand abstract material and the lack of utilization of learning media, so this study is motivated to obtain snakes and ladders learning media to improve students' understanding of the material on Indonesian cultural diversity in a more interactive and enjoyable way. This study aims to produce valid, practical and effective snakes and ladders learning media. The method used in this study is the 3D model (Define, Design, Development). This 3D model is very identical to the development of a product for use in learning. The results of the study show that the snakes and ladders learning media developed in this study fall into the very valid criteria. There are 3 aspects assessed in this validity, namely media validity, material validity, language validity. From the three validations, a validity value of 89.3% was obtained with the criteria "very valid". Based on the one-to-one trial of the student questionnaire, the practicality value was obtained at 99.6% with the criteria "very practical" and based on the small group trial, the value was obtained at 99.5% with the criteria "very practical" and the test effectiveness trial obtained a value of 86.36% with the criteria "very effective". So the development of this snake and ladder learning media is declared valid, practical, and effective.